Pelatihan Preceptorship dan Mentorship bagi pembimbing klinik di rumah Sakit - Ikawati Setyaningrum,; Wisnu Widyantoro,; Agus Budianto,; Deni Irawan,; Nurhakim Yudi Wibowo,; Yessy Pramita Widodo, (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
The nursing education process was implemented through clinical practice in hospitals. However, the heavy workload of nurses and clinical instructors often hindered the optimal provision of guidance to students. Therefore, efforts were necessary to enhance the competencies of nursing educators and clinical instructors. The development of these competencies required support from both formal and non-formal education. One form of non-formal education was the implementation of preceptorship and mentorship training programs. These programs were expected to strengthen the quality of student guidance in clinical settings. The methods employed included lectures, role-playing, and hands-on application in inpatient care units. The training outcomes indicated a significant improvement in the clinical instructors’ ability to effectively carry out preceptorship and mentorship roles.